Ojcowie: Wincenty Pol i Gustaw Zieliński - Król, Małgorzata Maria (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This article approaches the relationship of the 19th century fathers (Wincenty Pol and Gustaw Zieliński), with their children. The analysis of their correspondence, supports the theory, that they both participated in the lives of their loved ones, rather only by letters. Both fathers, men-institution, figures important in the Polish then society, involved in public duties, did not have enough chances to fully participate in reaching adolescence by their children. Stays with their families, about which testimony can be found (in already published corrspondence of Wincenty Pol, and for the first time being made public Gustaw Zieliński’s letters) – were filled with preparations for further journeys, expeditions, research works, and planned events. Such lack of their presence was compensated by regular correspondence.